Case Report: Locally invasive thyroid metastases from renal cell carcinoma: surgery after neoadjuvant therapy - Hartl, Dana M.; Bani, Mohamed-Amine; Ghuzlan, Abir Al; Simonescu, Andreea-Elena; Breuskin, Ingrid; Marhic, Alix; Albiges, Laurence; Lamartina, Livia; Hadoux, Julien (Frontiers in Oncology, 2025)
ObjectiveNeoadjuvant therapy is under investigation not only for unresectable clear cell renal cell carcinoma (ccRCC) (1) but also for locally invasive primary thyroid cancers (2). Herein, we describe two cases of locally invasive thyroid metastases from ccRCC treated surgically after neoadjuvant therapy to highlight the rationale and outcomes.Patients and methodsTwo patients, one woman and one man, both age 69, developed unresectable thyroid metastases from ccRCC, respectively, 20 and 13 years after nephrectomy for ccRCC. Patient 1 received lenvatinib and a bispecific anti–Programmed cell Death protein 1/ cytotoxic T-lymphocyte-associated protein 4 (PD-1/CTLA-4) antibody in the context of a clinical trial. The second patient received nivolumab and cabozantinib.ResultsThe observed tumor response in patient 1 showed a decrease in mean surgical complexity score from unresectable (prevertebral fascia invasion) to severe (risk of recurrent nerve paralysis) and in patient 2 from unresectable (prevertebral fascia) to moderate (superficial esophageal invasion). The recurrent nerve was invaded in patient 1, leading to a subtotal resection. Surgery was a total thyroidectomy extended to the internal jugular vein in patient 2. Hospitalization was 1 and 2 days, respectively. Postoperative dysphonia improved in patient 1 after 3 months. No complications occurred in the second patient, who received adjuvant radiation therapy. After surgery, systemic therapy was discontinued in both patients, and stable residual oligometastatic disease was followed.ConclusionNeoadjuvant therapy enabled a macroscopic resection of locally invasive thyroid metastases, preserving laryngeal function and allowing discontinuation of systemic therapy. This approach may be considered in these rare cases, although the impact on progression-free or overall survival is currently unknown.